Detection of hypoglycemic drugs adulterated in herbal products with high-performance liquid chromatography - Lê, Thị Bảo Trâm; Tạ, Nguyễn Khánh Hà; Hoàng, Thị Minh Nguyệt; Phạm, Thị Thanh Hà; Nguyễn, Thị Kiều Anh; Nguyễn, Hải Phong; Huỳnh, Văn Chung; Đào, Thị Cẩm Minh (Hue University Journal of Science: Natural Science, 2023)
Circular No. 10/2021/TT-BYT stipulated that several hypoglycemic drugs, such as metformin hydrochloride, are prohibited from adulterating medicinal herbal preparations. Therefore, this study aims to develop a procedure to detect five hypoglycemic drugs, including metformin hydrochloride, glibenclamide, gliclazide, glimepiride, and glipizide, adulterated in herbal preparations by using the high-performance liquid chromatography (HPLC) method. The chromatographic program includes the methanol:phosphate buffer pH 3 mobile phase 70/30 (v/v), chromatographic column C18 (250 × 4.6 mm, 5 μm), and analysis time of 25 minutes. The procedure has high specificity, accuracy and precision, according to AOAC. We detected six herbal products reacting positively with glibenclamide and one with both metformin hydrochloride and glibenclamide.